Reducing the optical reflectance of kerf-loss free siliconwafers via auto-masked cf4/o2 plasma etch - Kim, Suhyun; Kim, Jun Hyun; Kim, Jihyun; Kim, Chang Koo (ECS Journal of Solid State Science and Technology, 2018)
Kerf-loss free (KLF) silicon can significantly contribute to the cost competitiveness of solar cells by reducing the amount of material wasted as the kerf loss during sawing process. Different techniques to produce KLF silicon wafers have been therefore studied, however, the fabrication processes for high efficiency solar cell with KLF wafers need further research. Since one of the major factors that decides the cell efficiency is the optical reflectance, the surface modification step such as anti-reflection coating or surface texturing process is necessary. In our experiment, auto-masked CF4/O2 plasma etching was used to obtain textured silicon surface with reduced reflectivity. As the bias voltage of CCP mode was varied, the morphology and the etch rate of the plasma-etched KLF silicon wafers were investigated. The reduction in the measured reflectivity demonstrated the effectiveness of the auto-masked texturing process on a KLF silicon wafer. These results will eventually attribute to providing cost-effective silicon solar cells.
Keywords: Cell efficiency; Cost competitiveness; Fabrication process; High-efficiency solar cells; Optical reflectance; Sawing process; Silicon surfaces; Surface-texturing